Shear Behavior of Reinforced Concrete Inverted-T Deep Beam - Hoda Shousha; Rasha T. S. Mabrouk; Akram Torkey (Salehan Institute of Higher Education, 2023)
Contrary to top-loaded deep beams, Inverted-T (IT) deep beams are loaded on ledges at the beam’s bottom chord. The presence of the load near the bottom of the beams creates a tension field in the web at the loading points. An experimental investigation was carried out in which 8 specimens of reinforced concrete IT deep beams were tested and the effect of the following variables was studied: changing the hanger diameter, hanger arrangement in terms of spacing and distribution distance, hanger reinforcement ratio, vertical and horizontal web shear reinforcement diameter, and spacing. In addition, all the tested beams had long ledges extending to the end of the beam. It was concluded that hanger reinforcement diameter and horizontal web shear reinforcement have an insignificant effect on the IT deep beam capacity. While the change in hanger arrangement, vertical web reinforcement, and ledge length has a significant effect on IT deep beam capacity. The maximum spacing of the hanger reinforcement and the minimum hanger reinforcement ratio passing through the load plate length will be studied in the following publication. A finite element model (FEM) was presented to predict the behavior of IT deep beams. The simulation was carried out using the ABAQUS 2017 software program. The results of the numerical model showed good agreement with the experimental program. Analysis using design codes was checked against the experimental data, where the computed beam capacities were compared to those obtained from the test results. The comparison showed a remarkable difference between the predictions using the design codes and the test results. Computation using design codes significantly underestimated the capacities of the beams. Doi: 10.28991/CEJ-2023-09-05-04 Full Text: PDF